A new deep-water species of the alpheid shrimp genus Salmoneus Holthuis, 1955 (Decapoda: Caridea) from East Flower Garden Bank off Texas, USA - Anker, Arthur; Flores, Paula C. Rodríguez; Nizinski, Martha S. (Zootaxa, 2025)
Salmoneus karenae sp. nov. is described based on a single specimen found in debris recovered from a depth of 84.9 m, in the East Flower Garden Bank off Texas, USA. The new species is unique within Salmoneus Holthuis, 1955 in having a domed carapace combined with completely exposed eyestalks and pale orange colour of the body and appendages. It represents the 14th species and first deep-water member of the genus in the western Atlantic.